2017
DOI: 10.1371/journal.pone.0188235
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of HIV-associated excess mortality by antiretroviral treatment among tuberculosis patients in Kenya

Abstract: BackgroundMortality from TB continues to be a global public health challenge. TB ranks alongside Human Immunodeficiency Virus (HIV) as the leading infectious causes of death globally. HIV is a major driver of TB related morbidity and mortality while TB is the leading cause of mortality among people living with HIV/AIDS. We sought to determine excess mortality associated with HIV and the effect of antiretroviral therapy on reducing mortality among tuberculosis patients in Kenya.MethodsWe conducted a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 36 publications
9
30
1
Order By: Relevance
“…In 2016 alone, the SSA region accounted for an estimated 86% of HIVlinked TB deaths (18). Kenya is one of the countries in SSA severely hit by the dual epidemic and appears among the WHO high TB and TB-HIV burden countries ranking 13 out of the 22 countries globally (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016 alone, the SSA region accounted for an estimated 86% of HIVlinked TB deaths (18). Kenya is one of the countries in SSA severely hit by the dual epidemic and appears among the WHO high TB and TB-HIV burden countries ranking 13 out of the 22 countries globally (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…million incidences of TB annually [50,51]. They have a close link even though their biological co-existence and co-dynamics vary regionally with much burden in Sub-Saharan Africa [31,52].…”
Section: Discussionmentioning
confidence: 99%
“…One such study in Korea observed similar results with a median survival time of 21 days [13]; another study found that 19% of the patients died within 7 days and 41% died within the first month after the start of treatment for TB [14]. Another study, performed in Africa, found a mean survival span of two months in 53.3% of the people who started their TB treatment; in this case, mortality among HIV-positive people was higher than for those who were HIV-negative or whose HIV status was unknown [3].…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the technique of survival analysis have found that death from TB is most common in the first three months after diagnosis among patients with coinfection with human immunodeficiency virus and TB (TB/HIV) [8], while another study observed that the majority of deaths took place within two months after the start of treatment for TB [3]. A study investigating an HIV-negative population found that the median survival was 12 days, considering those who died of TB [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation